Integration Strategy to Improve Competitive Advantage and Marketing Performance of Culinary MSMEs in Ambon City - Tabelessy, Walter (International Journal of Applied Economics, Accounting and Management (IJAEAM), 2024)
In the dynamic era of globalization, Micro, Small, and Medium Enterprises (MSMEs) in Indonesia face major challenges in achieving competitive advantage. MSMEs, which also play an important role in the national economy, often find it difficult to adapt to the latest trends such as digital marketing. Digital marketing provides great opportunities for MSMEs to expand market reach and increase interaction with consumers, but its effectiveness in increasing competitive advantage is still debated. This study examines how the integration of digital marketing, product innovation, and customer relationship management (CRM) funds can strengthen the competitive advantage of MSMEs, especially in the culinary sector in Ambon City. Using the Partial Least Square Structural Equation Modeling (PLS-SEM) method, this study involved 155 culinary MSME actors to test the three elements against competitive advantage and marketing performance. The results showed that digital marketing, product innovation, and CRM significantly influenced competitive advantage, which also had a positive impact on marketing performance. These findings support the importance of holistic strategy integration to increase the competitiveness of MSMEs in the global market and provide insights for the development of relevant theoretical models